PEMBERDAYAAN KELOMPOK PENDUKUNG ASI EKSKLUSIF DALAM GERAKAN GEMAR ASI EKSKLUSIF - Rina Sri Widayati; Istiqomah Risa Wahyuningsih (WARTA LPM, 2016)
The gold standard in infant feeding and child starting from Early Initiation of Breastfeeding (IMD), exclusive breastfeeding for the six months. One of the health problems faced in the area of †health centers Pucang Sawit is the lack of motivation of counselor support group exclusive breastfeeding. There are only three groups motivator breastfeeding support so not comparable with the number of babies in the region Pucang Sawit. Approaches through peer (Peer Support) on exclusive breastfeeding support group as one of the community-based empowerment efforts so as to help improve coverage eksklusive breastfeeding in Surakarta close to the target so that the vision of becoming a pilot Surakarta can be realized. Implementation ofservice programs are divided into three programs: the first socialization to the cadre and peer group as well as breastfeeding support group facilitator conducted one day, both the implementation of training activities breastfeeding support group for 4 days which consists of four small groups and accompanied by two facilitators each and third activity is monitoring and evaluation results formations breastfeeding support groups.